The Effect Of Fear Of Missing Out (FOMO) And Viral Marketing On Consumer Shopee Purchasing Decisions In Generation Z In Tasikmalaya City - Sa'bani, Putri Sani; Lestari, Suci Putri; Asyiah, Ai Kusmiati (Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine the effect of Fear of missing out and viral marketing simultaneously or partially on consumer purchasing decisions at Genz in Tasikmalaya City using Shopee. The method used in this research is a survey method with a quantitative approach. The research data was obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple linear regression analysis using SPSS software. The results of this study indicate that fear of missing out and viral marketing have a significant effect simultaneously on purchasing decisions. Fear of missing out has no significant effect partially on purchasing decisions. Meanwhile, Viral marketing has a partially significant effect on purchasing decisions.